The use of acoustic control technology to improve the manufaturing process to foster better engineering environment - Saifull Nizar, Ahmad; Mohd Noor Arib, Md Rejab; Sazali, Yaacob; Fauziah, Mat (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.